Perencanaan Arsitektur Sistem Informasi Sekolah dengan Pendekatan Togaf-Adm dalam Penerapan Standar Nasional Pendidikan - Rizki, Fahlul; Kurnia, Ulfa Isni; Alfina, Alfina; Priyono, Priyono (Infotek: Jurnal Informatika dan Teknologi, 2024)
To help the School achieve SNP, enterprise architecture modeling brings its business strategy and technology together. The Open Group Architecture Framework (TOGAF) can be used as the framework to organize the structures and objects related to the organization in architectural modeling. A method, such as the Architecture Development Method (ADM), is also used to determine the Enterprise Architecture in detail.The goal of information system architectural design analysis is to get a clear image of the information system and better communicate to users how it will operate. In this study, a generic architectural model design connected to the organization's vision and goal was generated using the TOGAF technique as a tool for building and designing enterprise architecture. The study's findings point to a connection between various types of architecture, starting with business architecture, application architecture, and information system architecture, which can create a framework for constructing and developing integrated information systems in schools that can be used as a guide by all organizational units. The outcomes of combining the three primary activities' information system planning and application efforts will be used as tools to support the school's vision, purpose, and goals.